Kontribusi Sekolah Ekspor Dalam Membangun Kapasitas Calon Eksportir Melalui Program Merdeka Belajar Kampus Merdeka (MBKM) - Arif Ripansyah; Yuni Prihadi Utomo (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to analyze the role of Export Schools in increasing the capacity of prospective exporters in Indonesia through a project-based learning approach in the Merdeka Belajar Kampus Merdeka (MBKM) program. The main focus of this study is to identify the contribution of Export Schools in developing technical competencies, managerial skills, and cross-cultural understanding of students in the export sector. The research method used is Participatory Research, where students are actively involved in field-based export projects. The research findings show that Export Schools play a key role in forming new exporters who are competent and ready to compete in the global market. The project-based learning approach allows students to be directly involved in field practices, from managing export documents to managing international supply chains. This involvement contributes to improving technical skills and data-based decision making. Overall, the results of this study confirm that Export Schools make a significant contribution to strengthening the capacity of prospective exporters, supporting Indonesia's export competitiveness, and playing a role in achieving the national target of producing 500.000 new exporters by 2030.